Implementation of Crowdfunding Web Application Using AWS Amplify Architecture with End-to-End Testing Using Playwright - Utomo, Ary; Wijaya, Ganang; Setiawan, Yanto (International Journal Labs, 2023)
This research aims to address the challenges in fundraising processes, which often lack systematic and transparent approaches. To overcome these issues, a web-based crowdfunding application was developed using AWS Amplify as the cloud architecture, Next.js as the web application development framework, and Playwright as the automated end-to-end testing framework. Following the Agile Scrum methodology, the application was designed to provide a convenient and secure user experience for fundraising managers, donors, and potential beneficiaries. The evaluation results showed a high user satisfaction rate of 93.29%, indicating a significant improvement in fundraising effectiveness. Furthermore, the implementation of the web application resulted in a remarkable 210% increase in fundraising efficiency within a 19-day timeframe. The end-to-end automated testing, covering 11 test scenarios on various browsers such as Chromium, Firefox, and WebKit, demonstrated successful performance within a short testing time of 1.9 minutes. These findings validate the success and benefits of the developed web application, offering improved fundraising capabilities and high user satisfaction.